Integrasi Pengetahuan Lokal dalam Pendidikan Seni Rupa di Era Digital - Muhsin Ilhaq; Irfan Kurniawan (Jurnal Sitakara, 2023)
This study aims to explore the integration of local knowledge in art education in the city of Palembang in the digital era. Using a phenomenological approach with qualitative methods, this study examines how digital technology and cultural heritage can be integrated into the art education curriculum. Results indicate that although there are challenges in adapting to technology, its proper application can enrich students' understanding of traditional arts and prepare them for the digital era. It can be concluded that effective art education in the modern era should consider cultural heritage while leveraging technological innovations. Keyword: Art education, local knowledge integration, digital era